2013
DOI: 10.1371/journal.pone.0080329
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in Life Predicts Better Emotional Recovery from Negative Stimuli

Abstract: Purpose in life predicts both health and longevity suggesting that the ability to find meaning from life’s experiences, especially when confronting life’s challenges, may be a mechanism underlying resilience. Having purpose in life may motivate reframing stressful situations to deal with them more productively, thereby facilitating recovery from stress and trauma. In turn, enhanced ability to recover from negative events may allow a person to achieve or maintain a feeling of greater purpose in life over time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
125
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 51 publications
6
125
0
1
Order By: Relevance
“…In prior research, individuals with greater purpose in life prospectively demonstrated reduced risk of stroke, myocardial infarction, metabolic syndrome, cerebral infarcts, Alzheimer disease pathology, and mortality and also increased use of preventative health services (Boehm & Kubzansky, 2012; Boylan & Ryff, 2015; Boyle et al, 2012; Cohen, Bavishi, & Rozanski, 2016; Hill & Turiano, 2014; Kim, Strecher, et al, 2014; Kim et al, 2012, 2013; Ryff, 2014; Yu et al, 2015). Purpose in life has been linked with healthier automatic emotion regulation strategies (Schaefer et al, 2013) and sustained activity in reward circuitry (Heller et al, 2013), which may function as neural mechanisms linking purpose in life to physical health outcomes. Given the specificity of the inverse association between HbA1c to purpose in life, this construct may be ubiquitously protective across a number of physical health domains, and efforts to increase purpose in life, perhaps via volunteering or finding work in retirement (Barron et al, 2009; Greenfield & Marks, 2004; Weiss, Bass, Heimovitz, & Oka, 2005), may yield important physical health benefits across cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, individuals with greater purpose in life prospectively demonstrated reduced risk of stroke, myocardial infarction, metabolic syndrome, cerebral infarcts, Alzheimer disease pathology, and mortality and also increased use of preventative health services (Boehm & Kubzansky, 2012; Boylan & Ryff, 2015; Boyle et al, 2012; Cohen, Bavishi, & Rozanski, 2016; Hill & Turiano, 2014; Kim, Strecher, et al, 2014; Kim et al, 2012, 2013; Ryff, 2014; Yu et al, 2015). Purpose in life has been linked with healthier automatic emotion regulation strategies (Schaefer et al, 2013) and sustained activity in reward circuitry (Heller et al, 2013), which may function as neural mechanisms linking purpose in life to physical health outcomes. Given the specificity of the inverse association between HbA1c to purpose in life, this construct may be ubiquitously protective across a number of physical health domains, and efforts to increase purpose in life, perhaps via volunteering or finding work in retirement (Barron et al, 2009; Greenfield & Marks, 2004; Weiss, Bass, Heimovitz, & Oka, 2005), may yield important physical health benefits across cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological resources may represent the intrapersonal piece of reserve capacity, and together with other tangible and interpersonal resources, help low SES individuals cope with stressors (Gallo & Matthews, 2003). Regarding potential top-down mechanisms, psychological well-being, including purpose in life, has been linked to healthier brain functioning, such as greater left (than right) prefrontal activation profiles (Urry et al, 2004), faster automatic recovery from negative emotional stimuli (Schaefer et al, 2013), and sustained striatal and dorsolateral prefrontal cortex activity following positive stimuli (Heller et al, 2013). Together, the data support salubrious effects of psychological resources, and the moderation findings add to a growing body of literature that such resources are especially important for health among individuals with low, but not high, SES (Lachman & Weaver, 1998; Morozink et al, 2010; Turiano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Heller et al (2013) we showed that participants with longer duration ventral striatal responding to positive stimuli reported higher levels of psychological wellbeing and also showed lower levels of cortisol. In Schaefer et al (2013) we reported that participants with higher scores on the Purpose in Life subscale of wellbeing display faster recovery from negative stimuli. Are there other important metrics of affective chronometry that are associated with psychological and physical health?…”
Section: What Is the Relation Between The Time Course Of Posi-mentioning
confidence: 82%